O tambor como herança dos pretos: uma análise sobre o território quilombola de Santa Rosa dos Pretos - Silva, Joércio Pires da (2025)
In this work I seek to show the importance of Tambor de Crioula as an instrument of struggle and resistance in the face of the arrival of large companies in the quilombola territory of Santa Rosa dos Pretos, located in Itapecuru-Mirim, Maranhão. Through narratives of elders and my own experience as quilombola, I briefly review the history of the territory and the uses attributed to tambor in theory to highlight how it passes from "cultural expression" to an instrument of resistance. To this end I reconstruct the processes of black resistance as well as the formation of quilombola identity and the struggles hindered on behalf of the recognition of the territory in the face of the process of negation put in place by the State. Tambor de Crioula appears in this way as the focus of this study and a privileged analysis in order to understand the role of ancestrality in the struggle of these quilombos. For this purpose, the process of hearing the older people considered to be elders gave me the foundation necessary to understand the historicity of this black territory that has much to teach us